Islamic Values-Based HRM and Its Impact on Student Achievement in Islamic Education - Muhamad Faizin; Rudi Sulaeman; Cepi Budiyanto; Ilham Fahmi; Muchdjabir Wahid (Prodi Manajemen Pendidikan Islam Universitas KH Chalim Mojokerto, 2025)
This study aims to analyze the implementation of Islamic values-based management of teaching and educational staff and its impact on improving student academic achievement. This study employed a qualitative approach, utilizing a field study design involving 15 informants, comprising study program heads, lecturers, educational staff, and students. Data were collected through in-depth interviews, observations of academic activities, and reviews of performance documents and SOPs for human resource management, then analyzed using the Miles & Huberman interactive model. The results showed that the integration of Islamic values ​​​​contributed significantly to improving student achievement, with the average GPA increasing from 3.50 to 3.83 and the on-time graduation rate increasing from 78% to 93% in the last four years. Recruitment based on value alignment, competency development that combines pedagogical and ethical dimensions, and performance evaluation with moral and academic indicators has a positive effect on student motivation and achievement. The field findings show that the value of shura fosters participatory leadership and collective accountability; amanah enhances the personal integrity of teaching staff; ihsan promotes a culture of quality and learning innovation; while itqan serves as the basis for work excellence and academic rigor. Analytically, this finding extends the theories of Value-Based Human Resource Management and Transformational Leadership by incorporating an Islamic spiritual dimension, which has been shown to influence organizational behavior and student learning outcomes. The novelty of this research lies in the empirical evidence that the integration of Islamic values ​​into HRM functions at the study program level directly improves student achievement, and it presents a theoretical synthesis between modern educational management practices and Islamic spirituality that has previously been rarely empirically explored in the context of Islamic higher education in Indonesia.